Interprovincial food trade and water resources conservation in China - Deng, Chuxiong; Zhang, Guangjie; Li, Zhongwu; Li, Ke (The Science of the total environment, 2020)
A spatial mismatch in water and arable land availability results in large virtual water transfers through interprovincial food trade in China. Accurately identifying and measuring water-saving links in interprovincial food trade can help to relieve water resources pressure in main grain-producing areas. We use a multiregional input-output table combined with the CROPWAT model to build China's interprovincial virtual water transfer network embedded in food trade in 2012. Then, water saving and scarce water saving are measured. Both consider the difference in water productivity among provinces, but the latter also pays attention to the scarcity of water resources. Finally, we adopt a water footprint to recalculate the scarce water savings without precipitation (green water). Our results indicate that the amount of virtual water transfer embedded in food trade is 74.9 billion m3, which is equivalent to 12.22% of the total water use in 2012. We observe large variations in the relationship between water resources abundance and agricultural water-use efficiency across provinces. Especially, there is a virtual water transfer from provinces with high water productivity but a lack of water to provinces with low water productivity but an abundance of water. The scarce water saving can identify sustainable food trade links, which can alleviate water scarcity in consuming provinces without exacerbating water shortage in producing provinces. In addition, interprovincial food trade results in 15 billion m3 of scarce gray water saving, which is equivalent to 59.76% of the scarce blue water saving. Scarce water saving based on blue water and gray water provides a basis for establishing an interprovincial compensation mechanism to balance the cost of water redistribution caused by food trade. [Display omitted] •The interprovincial food virtual water trade network is constructed in China.•Water endowments is added to improve the calculation method of water saving.•The difference between water saving and scarce water saving is compared.•Water footprint is used to distinguish the saving of different types of water.•Important insights about coordinating food trade with sustainable water use.